(Guanidine) copper complex-catalyzed enantioselective dynamic kinetic allylic alkynylation under biphasic condition - Cui, Xi-Yang (2020)
Highly enantioselective allylic alkynylation of racemic bromides under biphasic condition is furnished in this report. This approach employs functionalized terminal alkynes as pro-nucleophiles and provides 6- and 7-membered cyclic 1,4-enynes with high yields and excellent enantioselectivities (up to 96% ee) under mild conditions. Enantioretentive derivatizations highlight the synthetic utility of this transformation. Cold-spray ionization mass spectrometry (CSI-MS) and X-ray crystallography were used to identify some catalytic intermediates, which include guanidinium cuprate ion pairs and a copper-alkynide complex. A linear correlation between the enantiopurity of the catalyst and reaction product indicates the presence of a copper complex bearing a single guanidine ligand at the enantio-determining step. Further experimental and computational studies supported that the alkynylation of allylic bromide underwent an anti-SN2' pathway catalyzed by nucleophilic cuprate species. Moreover, metal-assisted racemization of allylic bromide allowed the reaction to proceed in a dynamic kinetic fashion to afford the major enantiomer in high yield.